Gender differences in relation to symptoms of Attention deficit hyperactivity disorder (ADHD) among university students in Iceland - Viktoría Hulda Þorgrímsdóttir 2001- (2023)
Attention deficit hyperactivity disorder (ADHD) is a complex neurodevelopmental disorder characterized by excessive hyperactivity, inattention, and impulsivity that affect daily activities in children, adolescents, and adults. Previous studies have shown that ADHD symptoms can vary between genders as males tend to have more hyperactive symptoms and females tend to have more inattention symptoms. ADHD symptoms and comorbid disorders can affect the quality of life of those who have it. The aim of this study was to provide insight into gender differences in relation to symptoms among university students in Iceland. 471 out of 3,400 registered students at Reykjavík University participated in a survey called The Wellbeing of university students where 66 of them (14%) reported having been diagnosed with ADHD. Results showed that females were more likely than males to score higher on inattention symptoms and males were more likely than females to score higher on hyperactive symptoms, however, the difference was insignificant (p > 0,05). Results showed that those who score higher on the ADHD rating scale score higher on the depression and anxiety symptom scales while there was no significant association between ADHD score and self-esteem. These findings show that in this current study, there were no significant gender differences in ADHD symptoms, however, the findings also revealed that those diagnosed with ADHD are more likely to have some comorbid disorders. Keywords; gender differences, ADHD, inattention, hyperactivity, comorbid disorders Athyglisbrests- og ofvirkniröskun (ADHD) er flókin taugaþroskaröskun sem einkennist af ofvirkni, athyglisbrest og hvatvísi sem hefur áhrif á daglegar athafnir hjá börnum, unglingum og fullorðnum. Fyrri rannsóknir hafa sýnt að ADHD einkenni geta verið mismunandi milli kynja, þar sem karlar hafa tilhneigingu til að sýni meiri ofvirkniseinkenni en konur hafa tilhneigingu til að sýna meiri athyglisbrestsseinkenni. ADHD einkenni og samhliða sjúkdómar geta haft áhrif á lífsgæði ...